Análise da Confiabilidade em Redes de Distribuição Radiais: Reconfiguração e Alocação de Geração Distribuída - Coelho Neto, Agnelo (2006)
The distribution utilities must satisfy two concurrent objectives during planning process of the electric network: minimization of the investment cost and the satisfaction of reliability targets. An alternative to satisfy these objectives is to include low cost alternatives in the planning process. One of these alternatives is the reconfiguration of the distribution network. The reconfiguration of the distribution network can reduce the loss and balance the loads in the system only with opening and closing of switches without additional investment cost. In addition to reconfiguration, another alternative of low cost is the Distributed Generation (DG) allocation. This alternative became feasible due to the recent technological advances in the building of turbines that reduced significantly the costs of energy generation. In this way, the DG is a attractive option to satisfy the demand growth and minimize the costs associated with: building of new substations, feeder reconductoring and transformer upgrading. Consequently, is opportune to develop methodologies that include the reconfiguration and the DG in the planning of the distribution network. This dissertation presents the development of two methodologies for the planning of distribution networks: reconfiguration and optimal allocation of DG. The first part of the dissertation presents the development of the methodology for the network reconfiguration. Usually, the reconfiguration is carried out with the following objectives: minimization of the electric losses, voltage profile correction and load balancing between feeders. In this dissertation, in addition to these objectives, reliability constraints have been included in the reconfiguration methodology. This methodology is based on the combination of the following techniques: power flow algorithm, based on the Power Summation Method, to estimate the state of the network; analytic techniques to estimate the reliability indices and Tabu Search to identify the optimal topology. The second part of the research work presents the development of the methodology for the allocation of DG. This methodology has as objective to attend a forecasted demand level without violating operational constraints of the network (feeders loading and voltage drops) and minimizing the interruption costs through the DG allocation. These objectives are satisfied minimizing the cost/worth ratio between the installation/operation costs of DG and the costs associated with: interruptions, noncommercialized, energy purchases and electric losses. The minimization of the cost/worth ratio described above has been carried out by combining the following techniques: analytic approaches to estimate the impact of DG in the reliability indices, load flow algorithm to estimate the losses and violations in the operational constraints and genetic algorithms to maximize the cost worth ratio. The impact of the DG in the reliability indices has been considered including network constraints (voltage drop and feeder loading) in the predictive reliability model. The models and techniques proposed in this dissertation for the reconfiguration and DG allocation have been validated and applied in two large scale substations belonging to distribution network of the Electricity Utility of Maranhão - CEMAR. The results obtained with the algorithm of reconfiguration demonstrated that the proposed methodology was capable of reducing the losses in the feeders without deteriorating the reliability. Furthermore, the application of the methodology of DG allocation in the test system resulted in a cost/worth ratio lower than one.